PERANCANGAN SISTEM DOORLOCK MENGGUNAKAN RFID DAN ANDROID BERBASIS ARDUINO NANO - Gatot Santoso; Slamet Hani (IST AKPRIND Yogyakarta, 2018)
The more modern the technology turns out to be followed by the higher criminals in an area. The crime rate in Indonesia has increased from year to year. The types of crime found are also increasing, for example the rate of theft from year to year continues to increase. Therefore, the technology needed to avoid the theft, such as theft at home then use the automatic door locks.The use of RFID technology (Radio Frequency Identification) to automate the system of open-door muscle. With the solution then it is possible made a software using Arduino Nano program. Arduino Nano program is applied to create a security system that can work automatically, which can open the door by automatically using Android and RFID as inputs and also as a control. In the operation of this automatic door, not only rely on controls that use the backup system, but on the side of the control using servo and selenoid motors. So it will produce motor servo motion output becomes smooth.From the measurement of the input components, it can be seen in the standby RFID voltage condition of 3.3 V. While for the servo motor of 10.87 V and bluetooth of 3.3V - 5 V. The distance obtained from RFID measurements based on the tags made on RFID is 5 cm - 10 cm. As for bluetooth also based on the maximum distance bluetooth with android is 1 m - 12 m. The output of the buzzer will be active when the applied voltage is between 3.3 V - 5 V, if the voltage is less or exceeded then the buzzer does not work.